Clarification and development of advanced practice roles in a Swiss French university hospital: an action research study - Patrick Teixeira Machado; Manuela Eicher; Aurélie Delouane-Abinal; Sarah Kupferschmid; Marie-José Roulin (BMC Health Services Research)
Abstract Background The evolving healthcare landscape emphasizes the need for health systems to adapt to growing complexities, with new models of care enabling healthcare providers to optimize their scope of practice and coordination of care. Despite increasing interest in advanced practice, confusion persists regarding the roles and scopes of practice of healthcare providers, exacerbated by variations in regulations and titles. We sought to clarify the differences between specialized healthcare professionals, practitioners, and clinical specialists; to describe their roles; and to propose initiatives aimed at supporting the implementation of advanced practice within a university hospital. Methods An action research design was conducted in a Swiss university hospital by the deputy healthcare director, five clinical specialists, one nurse practitioner, one nurse specialist, and six managers. A multimethod approach was used to generate data, which included a literature review, meeting minutes, unstructured interviews, and a questionnaire assessing healthcare providers’ perceptions about the clinical specialist role. Semi-structured interviews and a group interview with nursing leaders from Swiss hospitals were conducted to understand their use of clinical roles at the advanced level. Unstructured interviews were reduced and organized into categories. Survey data were analyzed with descriptive statistics, and an inductive content analysis method was used for semi-structured interviews and the group interview. Results Managers and healthcare providers shared a vision of clinical specialists’ activities but emphasized the lack of clarity surrounding these functions. Role clarity was emphasized as crucial for sustainability of advanced practice. A model that defined healthcare specialist, practitioner, and clinical specialist roles was developed. It included title standardization, use of an implementation strategy, creation of a tool to facilitate profile selection, and implementation of a communication plan. Further initiatives aimed to enhance training funding, establish regulations, and optimize advanced practice implementation and governance within the hospital. Conclusions The study results encourage clarification of clinical roles to facilitate their implementation and optimize resources. They also suggest initiatives to support advanced practice implementation, such as a communication plan and an implementation strategy, reflection on the current governance model, and integration of advanced practice providers. Ongoing efforts involve collaboration with academics, managers, and discussions at the political level.